Prioritizing and Issues in the New Media Space - New Media and Old Agenda - باديس مصطفاوي (International Journal of Social Communication, 2025)
This research paper aims to analyze the nature of the factors influencing the prioritization and framing of issues within the new media environment, relying on the classical theoretical framework of agenda-setting theory. It offers a comparative perspective between the traditional media agenda and the digital agenda, focusing on the characteristics and key actors involved in shaping agendas in the context of new media platforms. These actors include content and distribution algorithms, influencers, content creators, the rise of citizen journalism, the proliferation of fake accounts and troll armies, as well as the widespread use of sponsored content. The paper also explores the challenges that hinder the formulation of a coherent media agenda in the digital sphere—chief among them the difficulty of verifying news sources and the rapid, continuous evolution of issues. One of the key conclusions drawn is the reconfiguration of symbolic power within the media landscape and the shift in the center of influence over media agendas. The integration of digital platforms by major traditional media institutions has allowed for the persistence of certain features of the traditional agenda, albeit through new actors, resulting in a hybrid and dynamic environment where traditional and emerging modes of influence coexist and intersect.